On the ages of bright galaxies ∼500 Myr after the big bang: insights into star formation activity at z ≳ 15 with JWST. Issue 1 (5th December 2022) - Whitler, Lily; Endsley, Ryan; Stark, Daniel P; Topping, Michael; Chen, Zuyi; Charlot, Stéphane
ABSTRACT: With JWST, new opportunities to study the evolution of galaxies in the early Universe are emerging. Spitzer constraints on rest-optical properties of z ≳ 7 galaxies demonstrated the power of using galaxy stellar masses and star formation histories (SFHs) to indirectly infer the cosmic star formation history. However, only the brightest individual z ≳ 8 objects could be detected with Spitzer, making it difficult to robustly constrain activity at z ≳ 10. Here, we leverage the greatly improved rest-optical sensitivity of JWST at z ≳ 8 to constrain the ages of seven UV-bright ($M_{\rm uv}\lesssim -19.5$ ) galaxies selected to lie at z ∼ 8.5–11, then investigate implications for z ≳ 15 star formation. We infer the properties of individual objects with two spectral energy distribution modelling codes, then infer a distribution of ages for bright z ∼ 8.5–11 galaxies. We find a median age of ∼20 Myr, younger than that inferred at z ∼ 7 with a similar analysis, consistent with an evolution towards larger specific star formation rates at early times. The age distribution suggests that only ∼3 per cent of bright z ∼ 8.5–11 galaxies would be similarly luminous at z ≳ 15, implying that the number density of bright galaxies declines by at least an order of magnitude between z ∼ 8.5–11 and $z \sim 15$ . This evolution is challenging to reconcile with some early JWST results suggesting the abundance of bright galaxies does not significantly decrease towards very early times, but we suggest this tension may be eased if young stellar populations form on top of older stellar components, or if bright z ∼ 15 galaxies are observed during a burst of star formation.